Commonality despite exceptional diversity in the baseline human antibody repertoire - Briney, Bryan; Inderbitzin, Anne; Joyce, Collin; Burton, Dennis R. (Nature (London), 2019)
In principle, humans can produce an antibody response to any non-self-antigen molecule in the appropriate context. This flexibility is achieved by the presence of a large repertoire of naive antibodies, the diversity of which is expanded by somatic hypermutation following antigen exposure 1 . The diversity of the naive antibody repertoire in humans is estimated to be at least 10 12 unique antibodies 2 . Because the number of peripheral blood B cells in a healthy adult human is on the order of 5 × 10 9 , the circulating B cell population samples only a small fraction of this diversity. Full-scale analyses of human antibody repertoires have been prohibitively difficult, primarily owing to their massive size. The amount of information encoded by all of the rearranged antibody and T cell receptor genes in one person—the ‘genome’ of the adaptive immune system—exceeds the size of the human genome by more than four orders of magnitude. Furthermore, because much of the B lymphocyte population is localized in organs or tissues that cannot be comprehensively sampled from living subjects, human repertoire studies have focused on circulating B cells 3 . Here we examine the circulating B cell populations of ten human subjects and present what is, to our knowledge, the largest single collection of adaptive immune receptor sequences described to date, comprising almost 3 billion antibody heavy-chain sequences. This dataset enables genetic study of the baseline human antibody repertoire at an unprecedented depth and granularity, which reveals largely unique repertoires for each individual studied, a subpopulation of universally shared antibody clonotypes, and an exceptional overall diversity of the antibody repertoire. A genetic study of the baseline human antibody repertoire, based on the circulating B cell populations of ten subjects, reveals universally shared antibody clonotypes within repertoires that are largely unique to the individual.